The shape of populism - Grdešić, Marko. (Ann Arbor, MI)
viii, 196 sayfa
Keywords: “The Shape of Populism examines socialist Serbia, then part of Yugoslavia, which in the late 1980s witnessed popular mobilization and an emergence of a populist discourse that both constructed and celebrated “the people.” Author Marko Grdešić uses quantitative and qualitative analyses to show how “the people” emerge in the public sphere. This book examines over 300 protests and analyzes them in conjunction with elite events such as party sessions. It examines over 1,600 letters-to-the-editor and political cartoons to reveal the populist construction of “the people.” Grdešić also relies on interviews with participants in populist rallies in the late 1980s to examine the long-term legacies of populism“ --